2021
DOI: 10.1063/5.0032377
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of reinforcement learning for the intelligent control of a microfluidic peristaltic pump

Abstract: We herein report a study on the intelligent control of microfluidic systems using reinforcement learning. Integrated microvalves are utilized to realize a variety of microfluidic functional modules, such as switching of flow pass, micropumping, and micromixing. The application of artificial intelligence to control microvalves can potentially contribute to the expansion of the versatility of microfluidic systems. As a preliminary attempt toward this motivation, we investigated the application of a reinforcement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…99,100 Abe, Oh-Hara, and Ukita built a proof-of-concept system for applying RL to the control of microvalving to set the flow rate of a persitstaltic pump. 101 A 3-valve state was modeled as a Markov process, and was used to simulate flow rates produced from different state cycles. While used for a simple system, this principle could be particularly impactful when applied to more complex microfluidic valving networks.…”
Section: Optimization Of Device Performancementioning
confidence: 99%
“…99,100 Abe, Oh-Hara, and Ukita built a proof-of-concept system for applying RL to the control of microvalving to set the flow rate of a persitstaltic pump. 101 A 3-valve state was modeled as a Markov process, and was used to simulate flow rates produced from different state cycles. While used for a simple system, this principle could be particularly impactful when applied to more complex microfluidic valving networks.…”
Section: Optimization Of Device Performancementioning
confidence: 99%
“…However, certain proposed models may be susceptible to variations in working conditions, leading to performance limitations. Abe et al 6 employed RL in the continuous decision‐making process for optimizing the phase of microperistaltic pumps. The findings indicated that RL performed effectively in the optimization of the pump actuation sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning [14][15][16] and Machine learning (ML) algorithms [17,18] improve the accuracy of microfluidic system performance because they process large amounts of data from experiments, field measurements, and large-scale numerical simulations [19] in fluid dynamics. Therefore, DL and ML facilitate modular and agile modeling frameworks for solving many problems in fluid mechanics, such as experimental data processing, reducedorder modeling, shape optimization, turbulence closure modeling, and control.…”
Section: Introductionmentioning
confidence: 99%